The Portraits Of Two Different Social Milieus Depicted In The Pariban: Idola Dari Tanah Jawa Movie - Lambok Hermanto Sihombing (MOMENTUM : Jurnal Sosial dan Keagamaan, 2022)
The movie of “Pariban: Idola dari Tanah Jawa” shows the setting of a metropolitan city, Jakarta and the beauty of Samosir Island in North Sumatra. The use of language uttered by the main character, Halomoan Brandon Sitorus who lives in Jakarta is totally different from his relatives who live in his hometown, North Sumatera. In this scientific article, the author aims to observe how the camera works and the dialogue contributes to our understanding of Halomoan’s life in his hometown on the contrary to his life in the city. In order to help the author doing this analysis, Mise En Scene approach from Manon de Reeper and Theory of Representation from Stuart Hall are used for this study. The result of this study shows that this film represents the portraits of two different social milieux, Jakarta and Samosir Island.